The decision making criteria of a rational investor on the example of an investment portfolio analysis of listed companies and a basket of currencies - Tadla, Karolina (Managerial Economics, 2024)
In today’s globalized world, investing is a key financial management strategy related to the hope of obtaining future economic benefits. Access to more and more information has created new opportunities for wealth creation, including investments in stocks, cryptocurrencies, gold, real estate and many other assets. The work emphasizes the importance of investing and diversifying the investment portfolio, especially in periods of inflation, using the example of a portfolio of listed companies compared to a currency portfolio. The study covers the period from December 2019 to December 2020, and the analysis aims to estimate the rate of return on investment based on the Markowitz and CAPM theories. The presented analysis method is applicable both in the academic environment and in real economic scenarios, encouraging further research on investments.